Activated Electron‐Transport Layers for Infrared Quantum Dot Optoelectronics. Issue 29 (28th May 2018) - Choi, Jongmin; Jo, Jea Woong; de Arquer, F. Pelayo García; Zhao, Yong‐Biao; Sun, Bin; Kim, Junghwan; Choi, Min‐Jae; Baek, Se‐Woong; Proppe, Andrew H.; Seifitokaldani, Ali; Nam, Dae‐Hyun; Li, Peicheng; et al.
Abstract: Photovoltaic (PV) materials such as perovskites and silicon are generally unabsorptive at wavelengths longer than 1100 nm, leaving a significant portion of the IR solar spectrum unharvested. Small‐bandgap colloidal quantum dots (CQDs) are a promising platform to offer tandem complementary IR PV solutions. Today, the best performing CQD PVs use zinc oxide (ZnO) as an electron‐transport layer. However, these electrodes require ultraviolet (UV)‐light activation to overcome the low carrier density of ZnO, precluding the realization of CQD tandem photovoltaics. Here, a new sol–gel UV‐free electrode based on Al/Cl hybrid doping of ZnO (CAZO) is developed. Al heterovalent doping provides a strong n‐type character while Cl surface passivation leads to a more favorable band alignment for electron extraction. CAZO CQD IR solar cell devices exhibit, at wavelengths beyond the Si bandgap, an external quantum efficiency of 73%, leading to an additional 0.92% IR power conversion efficiency without UV activation. Conventional ZnO devices, on the other hand, add fewer than 0.01 power points at these operating conditions. Abstract : An ultraviolet‐light (UV)‐activation‐free electron‐transport layer is developed via aluminum and chlorine hybrid doping on zinc oxide (CAZO). CAZO‐using infrared (IR) quantum‐dot solar cells exhibit an external quantum efficiency beyond the silicon bandgap of 73%, leading to an additional 0.92% IR power conversion efficiency without UV activation.